Legal basis for explaining the contractual terms of «Contra proferentem» - Unegenova, Zh.; Adilgazy, S.; Teleuev, G. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
Attention is drawn to the fact that in the legal practice of the Republic of Kazakhstan there is no possibility of interpreting a civil law contract using the principle of «contra proferentem» with the currently valid legal norms. In the legal literature of the Republic of Kazakhstan, there is a lack of special research that takes into account the development trends of a modern market society, the rules for interpreting a contract with the principle of «contra proferentem» in the legal systems of Western countries with developed economies. In such cases, a critical analysis of the rules of foreign law and the practice of its application that govern the process of interpretation of contractual requirements of the «contra proferentem» principle is relevant. This analysis is presented using examples of the practice of applying legal norms in Western countries. A review of domestic judicial practice allows us to conclude that many issues related to the interpretation of a civil contract, in particular those related to establishing the content of vague and ambiguous contracts, are faced by the courts of the Republic of Kazakhstan. It should be recognized that in the practice of the courts of the Republic of Kazakhstan such approaches have not yet been developed. In order to fill the gap in the interpretation of the content of a civil contract in the domestic legal system, this research project is based on foreign experience. In this article, the authors comprehensively analyzed the principle of «contra proferentem» in the institution of interpretation of contractual terms of a civil law contract in the country and made recommendations for increasing its effectiveness.